2009
DOI: 10.1155/2009/573404
|View full text |Cite
|
Sign up to set email alerts
|

BEP/SEP and Outage Performance Analysis of -Branch Maximal-Ratio Combiner for Fading

Abstract: Maximal-ratio combiner (MRC) performances in fading channels have been of interest for a long time, which can be seen by a number of papers concerning this topic. In this paper we treat bit error probability (BEP), symbol error probability (SEP) and outage probability of MRC in presence of κ-μ fading. We will present κ-μ fading model, probability density function (PDF), and cumulative distribution function (CDF). We will also present PDF, CDF, and outage probability of the L-branch MRC output. BEP/SEP will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…( It is shown in [15], that the sum of κ-μ squares is κ-μ square as well (but with different parameters), which is an ideal choice for MRC analysis. Then the expression for the pdf of the outputs of MRC diversity systems follows [15, eq.11]:…”
Section: κ-μ Channel and System Modelmentioning
confidence: 99%
“…( It is shown in [15], that the sum of κ-μ squares is κ-μ square as well (but with different parameters), which is an ideal choice for MRC analysis. Then the expression for the pdf of the outputs of MRC diversity systems follows [15, eq.11]:…”
Section: κ-μ Channel and System Modelmentioning
confidence: 99%
“…For this process, it is necessary to estimate the phase of the received signal, so this technique requires all the amount of the channel state information of the received signal, and separate receiver chain for each branch of the diversity system, which increases the complexity of the system. In [2,10], it is shown that the sum of -μ powers is -μ power distributed as well (but with different parameters), which is an ideal choice for MRC analysis. The expression for the pdf of the outputs of MRC micro-diversity systems is as follows [10]:…”
Section: System Modelmentioning
confidence: 99%
“…In [2,10], it is shown that the sum of -μ powers is -μ power distributed as well (but with different parameters), which is an ideal choice for MRC analysis. The expression for the pdf of the outputs of MRC micro-diversity systems is as follows [10]:…”
Section: System Modelmentioning
confidence: 99%
See 2 more Smart Citations